2023
DOI: 10.3390/ijms24065223
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on “Pleiotropic Benefits of Melatonin: From Basic Mechanisms to Disease”

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is a multifunctional hormone that is naturally produced from tryptophan and released rhythmically throughout the night by the pineal gland to regulate sleep–wake cycles [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…While this protective effect has been shown to be primarily receptor-mediated, 77 it could also be attributed to its pleiotropic effects on ER-stress signaling pathways. 74,75,80 For example, melatonin has been shown to preserve intestinal barrier function and restore SIRT1 and SIRT3 activity/protein expression in the small intestine of sepsis models. 81 Xu et al have shown that melatonin enhances NF-κB deacetylation, thereby reducing the inflammatory response, and oxidative stress.…”
Section: Targeting Er-stress In Mucositismentioning
confidence: 99%
See 1 more Smart Citation
“…While this protective effect has been shown to be primarily receptor-mediated, 77 it could also be attributed to its pleiotropic effects on ER-stress signaling pathways. 74,75,80 For example, melatonin has been shown to preserve intestinal barrier function and restore SIRT1 and SIRT3 activity/protein expression in the small intestine of sepsis models. 81 Xu et al have shown that melatonin enhances NF-κB deacetylation, thereby reducing the inflammatory response, and oxidative stress.…”
Section: Targeting Er-stress In Mucositismentioning
confidence: 99%
“…Interestingly, melatonin has been indicated to protect against surfactant‐induced, 76,77 and ethanol‐induced 78,79 increases in small intestinal mucosal permeability in rats, highlighting its potential as a treatment for a compromised intestinal mucosal barrier. While this protective effect has been shown to be primarily receptor‐mediated, 77 it could also be attributed to its pleiotropic effects on ER‐stress signaling pathways 74,75,80 . For example, melatonin has been shown to preserve intestinal barrier function and restore SIRT1 and SIRT3 activity/protein expression in the small intestine of sepsis models 81 .…”
Section: Therapeutic Strategies Targeting Er‐stress In Mucositismentioning
confidence: 99%